A moodle course to substitute resuscitation teaching in a medical curriculum during the COVID-19 pandemic: A prospective pilot study - Ettl, Florian; Schriefl, Christoph; Grafeneder, Jürgen; Thallner, Dominik Gabriel; Mueller, Matthias; Fischer, Eva; Schlegel, Raphael; Sigmund, Thorsten; Holzer, Michael; Schnaubelt, Sebastian (Frontiers in Public Health, 2022)
Background Face-to-face medical education was restricted during the COVID-19 pandemic, leading to alternative teaching methods. Moodle® (Modular Object-Oriented Dynamic Learning Environment) – an online course format – has not yet been sufficiently evaluated for its feasibility and effectiveness in teaching cardiopulmonary resuscitation. Methods Medical students in the eighth semester took part in a Moodle® course teaching basic life support, the ABCDE-approach, airway management, and advanced life support. The content was presented using digital background information and interactive videos. A multiple-choice test was conducted at the beginning and at the end of the course. Subjective ratings were included as well. Results Out of 594 students, who were enrolled in the online course, 531 could be included in this study. The median percentage of correctly answered multiple-choice test questions increased after completing the course [78.9%, interquartile range (IQR) 69.3–86.8 vs. 97.4%, IQR 92.1–100, p < 0.001]. There was no gender difference in the median percentage of correctly answered questions before (female: 79.8%, IQR 70.2–86.8, male: 78.1%, IQR 68.4–86.8, p = 0.412) or after (female: 97.4%, IQR 92.1–100, male: 96.5%, IQR 92.6–100, p = 0.233) the course. On a 5-point Likert scale, 78.7% of students self-reported ≥4 when asked for a subjective increase in knowledge. Noteworthy, on a 10-point Likert scale, male students self-reported their higher confidence in performing CPR [female 6 (5–7), male 7 (6–8), p < 0.001]. Conclusion The Moodle® course led to a significant increase in theoretical knowledge. It proved to be a feasible substitute for face-to-face courses – both objectively and subjectively.